Exploring linkages between protected-area access and Kenyan pastoralist food security using a new agent-based model - Rekha Warrier; Randall B. Boone; Patrick W. Keys; Kathleen Galvin (Ecology and Society, 2024)
Pastoral communities living in the arid and semi-arid lands of Kenya raise livestock herds within highly patchy environments, and experience chronic food insecurity and inter-ethnic conflicts linked to resource access. For these primarily rural communities, livestock are a source of calories and income and are therefore crucial to achieving the United Nations’ Sustainable Development Goals (SDGs) associated with food security (SDG 2). Achieving sustainable improvements in household well-being in this region is contingent on understanding how diverse policy decisions complement or undermine the ability of pastoral households to raise livestock. Of near-term relevance is the question of reconciling food security with biodiversity conservation goals (SDG 15) across Kenya’s drylands, which are also known for their exceptional biodiversity. World over, protected areas are associated with diverse impacts on local communities. However, spatial variation in how these areas contribute to pastoral food security and household well-being across Kenya remain poorly understood. Using our newly developed model SPIRALL, we examined spatial variation in changes in household well-being that result when pastoral households across Kenya lose access to neighboring protected areas. SPIRALL is a country-scale, agent-based pastoral household decision-making model. We joined SPIRALL to L-Range, a model that simulates rangeland ecosystem functioning. The resulting coupled model simulates reciprocal interactions between pastoral households and the environment in Kenya and can be used as a scenario analysis tool to understand impacts of broadly defined policies on food security. Our scenario-based analysis showed that loss of protected-area access caused increases in rates of hunger, debt, and trans-boundary movements, particularly among non-sedentary and agropastoral households. These effects were spatially heterogeneous and influenced by county size and proximity to protected areas. We conclude by outlining the policy-implications result of the interactions between SDG 2 and SDG 15 in Kenya. We also highlight additional uses and avenues for improvement for SPIRALL.